Cereal-based proteins: Bridging health, sustainability, and future innovations for food industries - Sartagoda, Kristel June D.; Tiozon, Rhowell Jr.N.; Sreenivasulu, Nese (Elsevier, 2024)
The surge of interest in plant-based proteins and its positive impact on planetary health and environmental sustainability emphasizes the significance of cereal-based proteins for the food industry. Cereals are increasingly recognized not only for their vital role in meeting the growing demand for calories but also for dietary protein for their emerging nutraceutical benefits, offering potential solutions to human health. This work reviews current research and innovations in the landscape of the nutraceutical benefits of cereal proteins and peptides, encompassing antioxidant, anti-aging, anti-inflammatory, and anti-obesity properties, offer promising avenues for enhancing human health and addressing chronic diseases. Advanced techniques such as proteomics, have been widely applied to unravel the nutritional benefits of cereals, assess product quality and safety, and drive innovation in functional foods. The advancements in this field of plant protein research catering to the expanding needs of the food industry while emphasizing sustainability practices. The knowledge presented in this review will advocate for the widespread adoption of plant-based cereal proteins, aligning health, sustainability, and innovation.